Ayurveda management of severe coronary artery calcification in a triple vessel disease patient - a case report - Divya Kajaria; Punam N. Khobarkar (Journal of Ayurveda and Integrative Medicine, 2025)
The coronary artery calcium score is a tool for predicting the risk of coronary artery disease (CAD). Severe coronary artery calcification, particularly in the context of triple vessel disease, poses a considerable therapeutic difficulty for standard medical procedures. The treatment modality for heavily calcified coronary arteries is coronary stenting or coronary artery bypass grafting. Severe calcification reduces the efficacy of stent deployment during PCI. Severe coronary calcification complicates the surgical revascularization process, often leading to increased procedural risks and reduced long-term success rates. A 65-year-old female patient having severe coronary artery calcification (triple vessel disease) is treated with holistic Ayurveda management. It is observed that there is a 17.78 % decrease in the calcium score after purgation therapy and an additional 25.01 % decrease in the calcium score after Rasayana therapy.